The role of dietary magnesium deficiency in inflammatory hypertension - Pitzer Mutchler, Ashley; Huynh, Linh; Patel, Ritam; Lam, Tracey; Bain, Daniel; Jamison, Sydney; Kirabo, Annet; Ray, Evan C. (Frontiers in Physiology, 2023)
Nearly half of adults consume less than the estimated average daily requirement of magnesium (Mg2+), and commonly used medications, such as diuretics, promote Mg2+ deficiency. Consequently, chronic Mg2+ deficiency is widespread. Higher serum Mg2+ levels, increased dietary Mg2+ intake, and Mg2+ supplementation is each associated with lower blood pressure, suggesting that Mg2+ deficiency contributes to the pathogenesis of hypertension. However, the mechanisms by which Mg2+ deficiency increases blood pressure remain unclear. A high salt diet is also well-known to promote hypertension. Salt-induced inflammatory activity in antigen-presenting cells (monocytes and dendritic cells) in kidneys and blood vessels has been suggested to play a key role in salt-sensitive hypertension. In these cells, processes implicated as necessary for increased blood pressure include activation of the NLRP3 inflammasome, IL-1β production, and oxidative modification of fatty acids such as arachidonic acid, forming isolevuglandins (IsoLGs). Mg2+ deficiency also stimulates inflammation. We hypothesized that increased blood pressure in response to dietary Mg2+-depletion leads to increased NLRP3, IL-1β, and IsoLG production in antigen-presenting cells. We found that a Mg2+-depleted diet increased blood pressure in mice. Mg2+-depleted mice did not exhibit an increase in total body fluid, as measured by quantitative magnetic resonance. Plasma IL-1β concentrations were increased. Using flow cytometry, we observed increased NLRP3 and IL-1β expression in antigen-presenting cells from the spleen, kidney, and aorta. We also observed increased IsoLG production in antigen-presenting cells from these organs. Primary culture of CD11+ dendritic cells confirmed that low extracellular Mg2+ exerts a direct effect on these cells, stimulating IL-1β production. These data demonstrate that a Mg2+ deficiency-induced increase in blood pressure in mice is associated with increased NLRP3, IL-1β, and IsoLG production in antigen-presenting cells and that extracellular Mg2+-depletion directly influences antigen-presenting cell activity, suggesting that inflammatory activity resulting from dietary Mg2+-depletion promotes hypertension.